2020
DOI: 10.3390/jcm9113733
|View full text |Cite
|
Sign up to set email alerts
|

The Body I Live in. Perceptions and Meanings of Body Dissatisfaction in Young Transgender Adults: A Qualitative Study

Abstract: Body dissatisfaction in individuals with Gender Incongruence (GI) represents a primary source of suffering. Several studies have highlighted how this suffering has psychological, physical, and biological implications. This work aims to explore experiences related to body dissatisfaction and investigate the issues associated with living in a body perceived as incongruent for individuals with GI. Thirty-six individuals, aged between 18 and 30 years old and at stage T0 of hormone treatment, participated in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Generally, the difficulties reported in the literature are internalizing in nature (e.g., depression, anxiety, eating disorder) [ 6 , 18 , 19 ]; however, there is considerable variability in the results across studies [ 17 ]. Research has shown that trans youths are at higher risk of self-harm, suicidal ideation, and suicidal attempts [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and that the well-being of these youths can be hindered by “internal” sources, such as body dissatisfaction or distress [ 30 , 31 , 32 , 33 , 34 ]. As Ristori and Steensma [ 17 ] noted, a significant proportion of these psychological problems may be understood as a response to the discrimination experienced by gender diverse youths, as conceptualized by the minority stress model [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the difficulties reported in the literature are internalizing in nature (e.g., depression, anxiety, eating disorder) [ 6 , 18 , 19 ]; however, there is considerable variability in the results across studies [ 17 ]. Research has shown that trans youths are at higher risk of self-harm, suicidal ideation, and suicidal attempts [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and that the well-being of these youths can be hindered by “internal” sources, such as body dissatisfaction or distress [ 30 , 31 , 32 , 33 , 34 ]. As Ristori and Steensma [ 17 ] noted, a significant proportion of these psychological problems may be understood as a response to the discrimination experienced by gender diverse youths, as conceptualized by the minority stress model [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in mental health seems to be strongly linked to the physical changes induced by GAHT [3]. In a very recent study, participants reported that their feeling of "incongruence" increased as their repulsion towards their body did [62].…”
Section: Psychological Aspects In Transgender Women During Gender Aff...mentioning
confidence: 98%
“…Transgender people are often considered a psychologically vulnerable group compared to the general population, partly due to distress deriving from GI itself and partly to a non-inclusive cultural background, which might also include difficulties in accessing general healthcare and GAHT [ 1 , 2 ]. GAHT, in particular, is a paramount tool to alleviate the incongruence between biological and experienced gender and, therefore, any psychological burden arising because of it.…”
Section: Introductionmentioning
confidence: 99%